2020
DOI: 10.1021/jasms.0c00043
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Parasites Toxoplasma gondii and Besnoitia besnoiti, Unveiled in Single Host Cells Using AP-SMALDI MS Imaging

Abstract: The obligate intracellular apicomplexan parasites Toxoplasma gondii and Besnoitia besnoiti are important causes of disease in both humans and cattle. To date, effective specific treatments are lacking for both infections. To counteract severe symptoms leading to, e.g., disabilities and even abortion in the case of human toxoplasmosis and bovine besnoitiosis, novel targets are required for development of drugs and vaccines. A promising emerging technique for molecular characterization of organisms is high-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Scanning microprobe matrixassisted laser desorption ionization (SMALDI) mass was invented by Hubert, M. in 2002 (Spengler andHubert, 2002). It was further improved as atmospheric pressure scanning microprobe matrix-assisted laser desorption/ionization mass spectrometry (AP-SMALDI MS) for imaging (Vegvari et al, 2017;Bhandari et al, 2018;Bredehoeft et al, 2019;Kadesch et al, 2020;Mokosch et al, 2021;Mueller et al, 2021;Righetti et al, 2021), while atmospheric pressure MALDI ion sources AP-MALDI have also been developed for MSI (Guenther et al, 2011;Jackson et al, 2018;Keller et al, 2018) and achieved a lateral resolution at 1.4 μm (Kompauer et al, 2017).…”
Section: Classical Ion Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning microprobe matrixassisted laser desorption ionization (SMALDI) mass was invented by Hubert, M. in 2002 (Spengler andHubert, 2002). It was further improved as atmospheric pressure scanning microprobe matrix-assisted laser desorption/ionization mass spectrometry (AP-SMALDI MS) for imaging (Vegvari et al, 2017;Bhandari et al, 2018;Bredehoeft et al, 2019;Kadesch et al, 2020;Mokosch et al, 2021;Mueller et al, 2021;Righetti et al, 2021), while atmospheric pressure MALDI ion sources AP-MALDI have also been developed for MSI (Guenther et al, 2011;Jackson et al, 2018;Keller et al, 2018) and achieved a lateral resolution at 1.4 μm (Kompauer et al, 2017).…”
Section: Classical Ion Sourcesmentioning
confidence: 99%
“…Furthermore, MALDI ion resources can be easily coupled with high-resolution (resolving power) mass analyzers, such as TOF, FT-ICR, and Orbitrap, which provide high mass accuracy for MSI targets. During the recent years, with the developments of some new MALDI ion sources, such as atmosphere pressure AP-MALDI (Kompauer et al, 2017), AP-SMALDI (Vegvari et al, 2017;Bhandari et al, 2018;Bredehoeft et al, 2019;Kadesch et al, 2020;Mokosch et al, 2021;Mueller et al, 2021;Righetti et al, 2021), MALDI-2 (Soltwisch et al, 2015), transmission MALDI-2 (Niehaus et al, 2019), and nano laser probed-based laser desorption ionization (Meng et al, 2020), the lateral resolution of MALDI-MSI will possibly achieve nm or µm level for single cell and even subcellular scale imaging. Finally, the scanning speed of MALDI-MSI largely depends on the speed of MS detection, spectra recording and data processing.…”
Section: General Marks and Conclusionmentioning
confidence: 99%
“…In addition to proteomics (39), lipidomics analysis in T. gondii has been addressed in the last decade, revealing parasite-specific proteins and lipids, unraveling parasite-host interactions (45). Recently, Kadesch and collaborators (2020) (46) carried out a mass spectrometry imaging in Besnoitia besnoiti and T. gondii infection in primary bovine umbilical vein endothelial cells using atmospheric-pressure scanning microprobe matrix-assisted laser desorption/ionization (AP-SMALDI) mass spectrometry imaging (MSI), an emerging technique that provides high resolution and allows analysis of single cells, allowing a metabolomic characterization. This study has revealed biomolecular markers of infection in both parasites and has shown striking differences in the metabolites during infection between both parasites, despite their closer phylogenic relationship, related in particular to lipid classes such as phosphatidylcholines, phosphatidylethanolamines, phosphatidylglycerols, cardiolipins, phosphatidic acids, and phosphatidylinositol (46).…”
Section: Next-generation Technologies Omicsmentioning
confidence: 99%
“…Fixed pellets were immediately frozen in liquid nitrogen and stored at −80 • C until further use. 33 Also, BUVEC were seeded on glass coverslips (15 mm; Thermo Fisher Scientific) and allowed to grow until confluency. Then, cell layers were infected as described above.…”
Section: Preparation Of Cell Pellets and Cell Monolayersmentioning
confidence: 99%